2017
DOI: 10.1515/cclm-2017-0349
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric reference intervals for 29 Ortho VITROS 5600 immunoassays using the CALIPER cohort of healthy children and adolescents

Abstract: Complex reference value trends were observed across the pediatric age range for several biomarkers examined on Ortho VITROS immunoassays. The availability of VITROS immunoassay RIs will enable accurate laboratory test interpretation and diagnosis for the pediatric population. As recommended by the CLSI EP28-A3c guidelines, implementation of these RIs should be validated for each laboratory's local pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…This was particularly evident for progesterone, follicle-stimulating hormone (FSH), luteinizing hormone (LH) and PTH. More recently, CALIPER established age-and sex-specific reference intervals for 29 immunoassays using Ortho VITROS 5600 assays [18]. Although the age and sex trends in analyte concentration were similar to those observed using Abbott and Beckman assays, some analyte concentrations were higher or lower overall.…”
Section: Biochemical and Endocrine Markers Measured By Immunoassaymentioning
confidence: 82%
See 2 more Smart Citations
“…This was particularly evident for progesterone, follicle-stimulating hormone (FSH), luteinizing hormone (LH) and PTH. More recently, CALIPER established age-and sex-specific reference intervals for 29 immunoassays using Ortho VITROS 5600 assays [18]. Although the age and sex trends in analyte concentration were similar to those observed using Abbott and Beckman assays, some analyte concentrations were higher or lower overall.…”
Section: Biochemical and Endocrine Markers Measured By Immunoassaymentioning
confidence: 82%
“…The majority of direct reference interval studies used assays performed on Abbott ARCHITECT instrumentation, using the c8000 [9], the i2000 [10,12], or the ci4100 [14,17,20] model. Additional direct reference interval studies used LC-MS/MS [13,16], HPLC [15], UPLC [16], or Ortho VITROS 5.1 [16], Ortho VITROS 5600 [18] or Beckman Coulter DxI or Access 2 assays [11].…”
Section: Sample Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, limited studies are available regarding the best time point for blood sampling after GnRH stimulation in Korean children [ 7 , 11 , 12 , 13 , 14 ]. Previous studies reported differences in hormone concentration ranges of LH and FSH in different ethnic populations using different analytical platforms [ 15 , 16 ]. Previous studies conducted to evaluate the best time point for blood sampling after GnRH agonist application in populations other than Korean used different doses of GnRH agonist, limited numbers of male subjects, different LH cut-off values, and different analytical platforms to diagnose CPP [ 6 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Iron metabolism related laboratory indices including serum ferritin (SF), the most specific test that correlates with total body iron stores, as well as serum iron (SI) and total iron-binding capacity (TIBC), which is needed to calculate the transferrin saturation (TS) value. 46 In cases of iron deficiency, SF and iron concentrations fall with an increase in TIBC and a reduction in TS.…”
Section: Introductionmentioning
confidence: 99%